Merging diabolical points of a superconducting circuit - Leone, R.; Monjou, A. (Condensed Matter Physics, 2013)
We present the first theoretical study of the merging of diabolical points in the context of superconducting circuits. We begin by studying an analytically solvable four-level model which may serve as theoretical pattern for such a phenomenon. Then, we apply it to a circuit named Cooper pairs pump, whose diabolical points are already known. Представлено перше теоретичне вивчення злиття диявольських точок у застосунку до надпровiдних контурiв. Спочатку дослiджено аналiтично розв’язувану чотирирiвневу модель, яка може служити теоретичною основою такого явища. В подальшому ця модель застосовується до контура, який називають помпа куперiвських пар, з вiдомими диявольськими точками.